PENYULUHAN MANAJEMEN BISNIS SYARIAH PEMANFAATAN DIGITAL MARKETING WIRAUSAHA KELOMPOK TANI PADA MASA PANDEMI COVID-19 DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Ujang Buchori Muslim; Hasbi Ash Shiddieqy; Meisa Sriyani (SAHID EMPOWERMENT JOURNAL, 2022)
The increase in positive cases of the Covid-19 corona virus which was followed up with PSBB (Large-Scale Social Restrictions), made various parties seek to control the development of Covid-19, as well as take various ways so that economic activity could continue. One of them is with digital marketing media. Digital marketing media is an effective medium in the Covid-19 era. In this community service activity, counseling on digital marketing sharia business management was carried out in Cengal Village, Karacak Village, Leuwiliang District, Bogor Regency from July to August 2020. This activity is expected to be useful for improving the quality and capabilities of farmer groups as MSMEs in digital marketing marketing. Thus the marketing of MSME products becomes more optimal and has a wider reach